2004
DOI: 10.1097/01.tp.0000095898.40458.68
|View full text |Cite
|
Sign up to set email alerts
|

Retransplantation in patients with graft loss caused by polyoma virus nephropathy

Abstract: The characteristics and outcome in 10 patients who underwent retransplantation after losing their renal grafts to BK virus-associated nephropathy (BKAN) are described. The patients underwent retransplantation at a mean of 13.3 months after failure of the first graft. Nephroureterectomy of the first graft was performed in seven patients. Maintenance immunosuppression regimens after the first and second grafts were similar, consisting of a combination of a calcineurin inhibitor, mycophenolate mofetil, and predni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 12 publications
3
45
0
1
Order By: Relevance
“…Ramos et al (69) reported successful repeat transplantation in nine of 10 patients without recurrent BKVN. Womer et al (68) recently reported successful repeat transplantation in two patients despite active viremia.…”
Section: Short-and Long-term Graft Survivalmentioning
confidence: 99%
“…Ramos et al (69) reported successful repeat transplantation in nine of 10 patients without recurrent BKVN. Womer et al (68) recently reported successful repeat transplantation in two patients despite active viremia.…”
Section: Short-and Long-term Graft Survivalmentioning
confidence: 99%
“…Tubulointerstitial damage from direct and indirect effects of the virus and rejection after immunosuppression reduction lead to early graft loss or chronic dysfunction (46,48,51,53,80,86,94,95,124). In recipients who have advanced kidney disease or who have returned to dialysis from BKV nephropathy, retransplantation has been successful (125)(126)(127)(128)(129)(130). In most cases, transplant nephrectomy and/or studies to confirm no active viral replication have been performed.…”
Section: Retransplantationmentioning
confidence: 99%
“…Low-dose cidofovir has been used to treat BK nephropathy (143)(144)(145)(146). Renal toxicity may result, especially with calcineurin inhibitors, although it is unclear how much BK infection also contributes to the renal dysfunction.…”
Section: Bk Polyomavirusmentioning
confidence: 99%
“…Clinical studies are needed to further evaluate the efficacy of cidofovir in the treatment of BK nephropathy. Successful retransplantation has been achieved in patients with failed allografts, usually at least 6 to 12 mo after cessation of immune suppression (144,147). Leflunomide and derivatives and fluoroquinolone antimicrobials are under investigation for BK nephropathy.…”
Section: Bk Polyomavirusmentioning
confidence: 99%